2006
DOI: 10.1111/j.1750-3841.2006.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of α‐, γ‐, or δ‐Tocopherol during Soybean Oil Oxidation

Abstract: The decomposition of α‐, γ‐, or δ‐tocopherol in soybean oil during 24 d of storage at 50 °C was determined by high performance liquid chromatography (HPLC). The initial contents of α‐, γ‐, and δ‐tocopherol in soybean oil were 53, 750, and 268 ppm, respectively. The degradation rates of α‐, γ‐, and δ‐tocopherol for the first 10 d were 5.6%, 1.2, and 0.5% per day, respectively. The α‐tocopherol was completely destroyed in 16 d. The destructions of γ‐ and δ‐tocopherol were 28% and 17% after 24 d. The induction pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
26
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 29 publications
13
26
0
3
Order By: Relevance
“…Furthermore, previous research has shown degradation of tocopherol in refined tuna oil stored at 40°C (Chotimarkorn, Ohshima, & Ushio, 2005) and in soybean oil stored at 50°C (Player, Kim, Lee, & Min, 2006) due to autoxidation. Phenolic compounds were the major phytochemicals that were responsible for antioxidant activity of plant materials.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, previous research has shown degradation of tocopherol in refined tuna oil stored at 40°C (Chotimarkorn, Ohshima, & Ushio, 2005) and in soybean oil stored at 50°C (Player, Kim, Lee, & Min, 2006) due to autoxidation. Phenolic compounds were the major phytochemicals that were responsible for antioxidant activity of plant materials.…”
Section: Resultsmentioning
confidence: 96%
“…These values are in agreement with Player et al . (), who found that tocopherols in soybean oil are degraded in the order: α‐ > γ‐ > δ‐tocopherol and showed that there was no synergistic effect between the basil extract and TBHQ.…”
Section: Resultsmentioning
confidence: 97%
“…Comparing BE and mixture, it can be noted that BE treatment retained higher amounts of all isomers up to 20 h of heating, mainly isomers of a-, gand d-tocopherol, with 84.26; 80.67 and 93.14%, respectively, demonstrating that the basil extract was the biggest responsible for the protective effect, minimizing the degradation of tocopherols. These values are in agreement with Player et al (2006), who found that tocopherols in soybean oil are degraded in the order: a-> g-> d-tocopherol and showed that there was no synergistic effect between the basil extract and TBHQ. The fatty acid profile during the thermoxidation can be found in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…α‐Tocopherol was the most susceptible to oxidation among all the tocopherols and tocotrienols. Previous studies showed that α‐tocopherol degraded faster than γ‐tocopherol during the storage study of rapeseed oil and soybean oil (Lampi, Kataja, Eldin, & Vieno, ; Player, Kim, Lee, & Min, ). Besides that, Bruscatto et al.…”
Section: Resultsmentioning
confidence: 97%
“…α-Tocopherol was the most susceptible to oxidation among all the tocopherols and tocotrienols. Previous studies showed that α-tocopherol degraded faster than γ -tocopherol during the storage study of rapeseed oil and soybean oil (Lampi, Kataja, Eldin, & Vieno, 1999;Player, Kim, Lee, & Min, 2006). Besides that, Bruscatto et al (2009) reported that the extent of degradation of tocopherols in rice bran oil was complied with the order of α-tocopherol > (γ + β) > δ-tocopherol at 100 and 180°C, which showed that the α-tocopherol was the most susceptible to oxidize.…”
Section: Food Chemistrymentioning
confidence: 85%